2016
DOI: 10.1063/1.4939206
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical investigation of the influence of gold nanosphere size on the decay and energy transfer rates and efficiencies of quantum emitters

Abstract: Articles you may be interested inWe present in this contribution a comprehensive investigation of the effect of the size of gold nanospheres on the decay and energy transfer rates of quantum systems placed close to these nanospheres. These phenomena have been investigated before, theoretically and experimentally, but no comprehensive study of the influence of the nanoparticle size on important dependences of the decay and energy transfer rates, such as the dependence on the donor-acceptor spectral overlap and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 114 publications
1
29
0
Order By: Relevance
“…Research on colloidal plasmon-mediated ET systems has shown that plasmon coupling to the donor has a larger influence on the ET process, allowing for the acceptor to be placed further from the plasmonic component, thereby reducing the direct quenching of the acceptor [46,62]. Therefore the QW barrier thickness is another parameter that can be tuned to move from a regime of quenching to one of enhancement [57,65].…”
Section: Energy Transfer Using Ag Nanoparticle Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on colloidal plasmon-mediated ET systems has shown that plasmon coupling to the donor has a larger influence on the ET process, allowing for the acceptor to be placed further from the plasmonic component, thereby reducing the direct quenching of the acceptor [46,62]. Therefore the QW barrier thickness is another parameter that can be tuned to move from a regime of quenching to one of enhancement [57,65].…”
Section: Energy Transfer Using Ag Nanoparticle Arraysmentioning
confidence: 99%
“…An advantage of this colloidal system is that it utilizes simple processing techniques like spin coating that are easily scalable, however the placement of AgNPs is random which can influence the ET process and aggregation of the AgNPs needs to be overcome; having more isolated NPs could sharpen the LSP resonance giving an overall larger effect. In addition, having the AgNPs in an intermediate layer between the QDs and QW could provide even greater enhancement of the energy transfer efficiency [62,63].…”
mentioning
confidence: 99%
“…8,16 These studies inform the design of the experimental system. The influence of an Au nanosphere on the nonradiateve energy transfer efficiency has been numerically investigated using a Green's tensor formalism.…”
Section: Plasmon-enhanced Non-radiative Energy Transfer In Quantum Domentioning
confidence: 99%
“…The influence of an Au nanosphere on the nonradiateve energy transfer efficiency has been numerically investigated using a Green's tensor formalism. 16 The donor quantum emitter emission and acceptor quantum emitter absorption are overlapped, and can vary from 400 nm to 700 nm. Fig.…”
Section: Plasmon-enhanced Non-radiative Energy Transfer In Quantum Domentioning
confidence: 99%
“…Research has been done on optimization of FRET on DNA nanostructures that identifies labeling sites to achieve different levels of energy transfer [115,116], in super resolution microscopy [56,117], and plasmonics [118,119,120,121].…”
Section: Molecular Diagnosismentioning
confidence: 99%